Hes4: A potential prognostic biomarker for newly diagnosed patients with high‐grade osteosarcoma. Issue 5 (27th October 2016) - McManus, Madonna; Kleinerman, Eugenie; Yang, Yanwen; Livingston, John Andrew; Mortus, Jared; Rivera, Rocio; Zweidler‐McKay, Patrick; Schadler, Keri
Abstract: Background: Prognostic biomarkers for osteosarcoma (OS) at the time of diagnosis are lacking. Necrotic response of OS to preoperative chemotherapy correlates with survival and is determined 3–4 months after diagnosis. The purpose of this study is to identify biomarkers that will stratify patients into good or poor responders to chemotherapy at diagnosis and determine the role of potential biomarkers in OS pathogenesis. Procedure: Because OS may be caused by disruptions of osteogenic differentiation, and the Notch pathway is one regulator of bone development, we examined the link between Notch effectors, OS differentiation, and OS outcome. We probed the R2: Genomics Analysis and Visualization Platform for RNA expression levels of Notch targets in mixed high‐grade OS pretreatment biopsies. We used human OS cell lines in vitro and in mice to determine the role of the Notch target hairy/enhancer of split 4 (Hes4) in OS. Results: We found that in OS patients, high expression of Hes4 is correlated with decreased metastasis‐free and overall survival. Human OS cells that overexpress Hes4 are more immature and have an increased invasive capacity in vitro . This was not universal to all Notch effectors, as Hes1 overexpression induced opposing effects. When injected into NSG mice, Hes4‐overexpressing OS cells produced significantly larger, more lytic tumors and significantly more metastases than did control cells. Conclusions: Hes4 overexpression promotes a more aggressive tumor phenotype by preventing osteoblastic differentiation of OS cells. Hes4 expression may allow for the stratification of patients into good or poor responders to chemotherapy at diagnosis.